(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2025)
Many language learners struggle with long-term vocabulary retention due to stress, distraction, or ineffective memorization strategies. A growing number of learners report that reviewing vocabulary before sleep and revising it again upon waking significantly improves recall. This article explores the personal-experience-based method of nighttime vocabulary learning, its psychological foundations, and the reasons why morning review leads to stronger memory retention